Well-posedness and stability results in a Timoshenko-type system of thermoelasticity of type III with delay term - Dellali, Khadra; Rahmoune, Abdelaziz, Directeur de thèse (Laghouat : Université Amar Telidji - Département de mathématiques, 2024)
In this memory, we consider a one-dimensional linear thermoelastic system of Timoshenko type with delay, where the heat conduction is given by Green and Naghdi’s theory. We establish the well-posedness and stability of the system for the cases of equal and unequal speeds of wave propagation.